An Efficient Environmentally Friendly Composite Material Based on Carbonized Biological Cellulose/Paraffin: Thermal and Sustainable Properties Analysis. Issue 39 (16th October 2020) - Xu, Yunfei; Zhang, Xiaoguang; Huang, Zhaohui; Chen, Guo; Leng, Guoqin; Lin, Fankai; Zhang, Weiyi; Liu, Yangai; Fang, Minghao; Wu, Xiaowen; Min, Xin
Abstract: A shape‐stabilized composite phase change material (SS‐CPCM) with paraffin (PA) and biological porous carbon (BPC) was prepared. Freeze‐dried biological‐cellulose include abandoned pomelo peel (APP) and tangerine peel (ATP) were carbonized in vacuum at 800 °C to obtain BPC to be used as a matrix material to prevent PA leakage and enhance thermal conductivity. A vacuum impregnation process was utilized to obtain the SS‐CPCM. Scanning electron microscopy showed that BPC (carbonized APP is subsequently referred to as BPC1 and carbonized ATP as BPC2) has a porous, honeycomb‐like structure, and that the paraffin encapsulated by the pores is evenly distributed. The SS‐CPCM2 (made from ATP) had the highest thermal conductivity (2.10 W/m K), which is 1.89 and 10 times that of the SS‐CPCM1 (made using APP) and pure PA, respectively. Differential scanning calorimetry and thermo‐gravimetric analysis were applied to determine the thermal performance and thermal reliability of the SS‐CPCM. Therefore, the prepared SS‐CPCM has potential in the field of energy storage. Abstract : The average thermal conductivities measured for pure paraffin (PA), BPC1 and BPC2 (biological porous carbon) were 0.21, 0.25 and 0.31 W/m K, respectively. The thermal conductivity of SS‐CPCM1 (1.11 W/m K) was 5.29 times higher than that of pure PA, and the thermal conductivity of SS‐CPCM2 (2.10 W/m K) was 10 times higher than that of pure PA. This is a significant improvement compared with pure PA.